Due diligence: a panacea for health and safety risk governance?. Issue 1 (2nd January 2017) - Peace, Christopher; Mabin, Victoria; Cordery, Carolyn
Abstract: The failure of boards and individual directors to engage with and accept accountability for work health and safety (WH&S) has frequently been commented on as a contributory cause of high injury and fatality rates. New Zealand has been no exception to this record, having poor fatal accident rates when compared with other OECD countries. One mining accident in New Zealand in 2010 triggered the introduction of new legislation in New Zealand, requiring 'due diligence' of 'officers' of workplace health and safety. This paper reviews the background to the law change, highlights its focus on due diligence, and explores the meaning of 'officer'. A decision tree is presented to help show the relationship of the due diligence requirement to companies' legislation and other requirements. The wider duties of directors are briefly analysed before presenting a range of 'reasonable steps' that might enable an officer to claim they had exercised due diligence to ensure compliance with the WH&S responsibilities of a business or undertaking. The relationship of these options to knowledge management and potential for application of management by objectives is described before discussing compliance problems arising for officers in smaller businesses.